Fungsi Onan Dalam Masyarakt Batak Toba dan Pasar Di Era Globalisasi - Simamora, Chandra Susilo; Siahaan, Wempi (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2018)
The article attempts to argue the so-called traditional functions of onan (traditional market) in the Toba People (Batak Toba people) of North Sumatera and confront them with the values of globalization. In addition to economic function, onan also serves as an arena of political activity, law, judiciary, peace, security, a place to express feelings, magic-religious, social gatherings and other socio-cultural activities. However, the authors see that these values have faded away because of the values of globalization that profoundly effected our life today. A wise attitude to face the current globalization is so important that the cultural values that form the identity of a nation are not dominated by the values of globalization that tend to be westernized